Changes in the Peripheral Blood Treg Cell Proportion in Hepatocellular Carcinoma Patients After Transarterial Chemoembolization With Microparticles - Ren, Zhizhong; Yue, Yuanxun; Zhang, Yuewei; Dong, Jiahong; Liu, Ying; Yang, Xiaowei; Lin, Xin; Zhao, Xueqiang; Wei, Zhanqi; Zheng, Yu; Wang, Tianxiao (Frontiers in Immunology, 2021)
Objective Transarterial chemoembolization (TACE) stands for an ideal therapy for patients with intermediate stage HCC. This study was carried out to observe the effect of microparticles-transarterial chemoembolization (microparticles-TACE, m-TACE) on the immune function of hepatocellular carcinoma (HCC) patients by detecting the proportion of regulatory (Treg) cells in the peripheral blood of HCC patients before and after m-TACE, and to determine whether m-TACE has a positive regulatory effect on the immune function of HCC patients. Methods 33 HCC patients treated with Gelatn Sponge Microparticles (GSMs-TACE) were enrolled. Flow cytometry was used to determine the proportion of Treg cells and CD4+/CD8+ T cells in peripheral blood of HCC patients 1 day before GSMs-TACE, 1 to 2 weeks and 3 to 5 weeks after GSMs-TACE, respectively. Results The Tregs cell proportion of HCC patients was significantly higher than that of the healthy and cirrhosis controls and was associated with various clinical indicators of HCC patients. The Treg cell proportion in HCC patients with BCLC stage C was higher than that of stage B patients; The Treg cell proportion at 1 to 2 weeks postoperatively was 8.54 ± 1.27%, which was significantly lower than that before the GSMs-TACE. The Treg cell proportion at 3 to 5 weeks postoperatively was 7.59 ± 1.27%, which continued to decline. The ratio of CD4+/CD8+ T cells was 1.31 ± 0.56, 1.86 ± 0.73, 1.76 ± 0.58% (P<0.01) respectively. Conclusion These results indicated that m-TACE could exert a positive regulatory effect on the anticancer immune function of HCC patients, which may be used in combination with immune adjuvant therapies to enhance the efficacy of HCC.